Exploring the Factors Influencing Teachers’ Perceptions of Information and Communication Technology (ICT) Integration in History Teaching and Learning: A Case Study of Lesotho - Atang Thulo; Walter Sengai (Universal Education Jurnal Teaching and Learning, 2025)
The integration of information and communication technology (ICT) has the potential to enhance teaching and learning in History by improving learner engagement and access to diverse perspectives. This study explored the factors influencing teachers’ perceptions of ICT integration in History teaching and learning in Lesotho. A qualitative approach was adopted, using a multiple case study design. The sample comprised five History teachers from five secondary schools, purposively selected for their role in teaching History, with schools chosen for their accessibility. Data were collected through semi-structured interviews, conducted both face-to-face and via telephone, and analysed using thematic analysis with the support of ATLAS. ti software. The findings indicate that although teachers generally hold positive perceptions of ICT integration, effective use is constrained by limited ICT skills, inadequate and inaccessible resources, insufficient administrative and technical support, and limited professional development opportunities. The study concludes that ICT integration in History teaching and learning is shaped primarily by institutional and capacity-related factors rather than teachers’ attitudes alone.